Human rights in the emerging global order; a new sovereignty - "Mills, Kurt" (London, 1998)
Mills focuses on one of the most significant parts of the sovereignty debate on human rights and humanitarian issues and raises three interrelated questions. First, how are empirical processes and practices undermining traditional notions of sovereignty? These include actions by the United Nations and other organizations on behalf of human rights, such as humanitarian intervention, the movements of refugees and others across the borders, and increasing calls for communal self-determination. Second, taking into account the above question, and examining these issues from a normative political theory perspective, what should be the relationship between individuals, groups, states, and the international community with respect to the twin aspects of power and authority inherent in sovereignty? Third, what new or modified international institutions may be needed in the future to deal with these humanitarian issues?
Keywords: Human rights